2014
DOI: 10.1016/j.ejpal.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Perpetrator characteristics and blame attributions in a stranger rape situation

Abstract: Both real-life events and research show that rape victims are sometimes blamed for their victimization. The effect of perpetrator characteristics on victim blaming has rarely been studied. In an experiment using a community sample (N = 161), we investigated the effect of the perpetrator's previous conviction and age, as well as participants' gender and belief in a just world (BJW) on blame attributions using a vignette methodology. It was predicted that less victim blame and more perpetrator blame would be att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 31 publications
(44 reference statements)
3
24
0
Order By: Relevance
“…Nevertheless, it is worth noting that the correlations between constructs were higher for men than for women. This is not surprising as research has shown that women tend to express stronger disapproval of wife beating than men (Gracia et al, 2015;Sakalli, 2001;Valor-Segura et al, 2011) and also attribute less blame to the victim and more to the perpetrator (Strömwall, Landström, & Alfredsson, 2014) .…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, it is worth noting that the correlations between constructs were higher for men than for women. This is not surprising as research has shown that women tend to express stronger disapproval of wife beating than men (Gracia et al, 2015;Sakalli, 2001;Valor-Segura et al, 2011) and also attribute less blame to the victim and more to the perpetrator (Strömwall, Landström, & Alfredsson, 2014) .…”
Section: Discussionmentioning
confidence: 97%
“…Nonetheless, a large number of studies suggests that men are more likely to engage in victim blaming (e.g., Anderson & Lyons, 2005;Bendixen, Henriksen, & Nøstdahl, 2014;Black & Gold, 2008;Durán, Moya, Megías, & Viki, 2010;Ferrão, Gonçalves, Giger, & Parreira, in press;Gölge et al, 2003;Grubb & Harrower, 2009;Harrison, Howerton, Secarea, & Nguyen, 2008;Mitchell, Angelone, Kohlberger, & Hirschman, 2009;Paul, Kehn, Gray, & Salapska-Gelleri, 2014;Schneider, Mori, Lambert, & Wong, 2009;Strömwall, Landström, & Alfredsson, 2014;Yamawaki & Tschanz, 2005). …”
Section: An Overview Of Rape Victim Blaming Observer Gendermentioning
confidence: 99%
“…For example, men are more likely than women to blame the victim (Ewoldt et al, 2000;Funk, Elliott, Bechtoldt, Pasold, & Tsavoussis, 2003;Gamache, 2006;Yamawaki et al, 2012), although "male victims were more likely to be blamed than female victims" (Stewart & Maddren, 1997, p. 2;Whatley & Riggio, 1993). While men tend to blame the victim, women tend to attribute blame to perpetrators (Langhinrichsen-Rohling et al 2004;Strömwall, Landström, & Alfredsson, 2014) and "males and females attributed less blame . .…”
Section: Effect Of Personal Characteristics On Attribution Of Blame Tmentioning
confidence: 99%